Perspectives on the economic and political history of the Ross Sea - Basberg, Bjørn L.; Lintott, Bryan (The Polar Journal, 2023)
The paper analyses the economic and political history of the Ross Sea, where exploration, science, commercial exploitation, politics and adventure became highly interlinked and interwoven. Expedition accounts and the extensive literature on Antarctic history and politics inform the contextual aspects. The archives of the Norwegian whaling company A/S Rosshavet, established in 1923, and the United States of America and New Zealand archival material from the 1950s are key sources. From the first whaling season onwards, the impact of Antarctic whaling, and later scientific bases, highlights and illustrates the tensions between Antarctic commerce, territorial claims and international politics.
Keywords: Sørishavet; historie; hvalfangst; politikk; økonomi

Keynes, Trouton and the Hector Whaling Company. A personal and professional relationship - Basberg, Bjørn L (Business History, 2017)
John Maynard Keynes’ activities on the stock market are well known. One company in which he bought stocks was the Hector Whaling Company Ltd., London – a comparatively small and little known company founded in 1928. The director of this company was Rupert Trouton. He had worked with Keynes for the Government during the First World War, was his student at Cambridge, and became a close partner in the City from the 1920s and onwards. The reason why Keynes invested in Hector was obviously his association with Rupert Trouton. The first part of this paper explores briefly the development of the Hector Whaling Company and its origins in Norway. The main part analyses the relationship between Trouton and Keynes. The focus is on their co-operation relating to Hector Whaling, but their relationship regarding various other businesses, as well as on the personal level, is also described. The paper is based on studies of the Keynes archives in Cambridge as well as newly available archives of the Hector company. The analysis provides new insights to the more general question on the motivations and decisions behind Keynes’ stock market investments as well as the internationalization of the whaling industry in the 1920s and 30s.
Keywords: Sørishavet; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk; økonomi

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

Perspectives on the Economic History of the Antarctic Region - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2006)
Keywords: Antarktis; ekspedisjoner; fiskeindustri; forskning; hvalfangst; ressurser; turisme; økonomi; økonomisk historie

Næringer i hvalfangstens grenseland - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Christen Christensen; Sørishavet; historie; hvalfangst; hvalkokerier; hvalolje; næring; patenter; pelagisk; økonomi

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Hvorfor gikk det så greitt? Om nedleggelsen av hvalfangstnæringen i Vestfold - Vik, Kjell (Vestfoldminne, 1984)
Keywords: Sørishavet; Vestfold; historie; hvalfangere; hvalfangstindustri; hvalindustri; næring; pelagisk; sjøfolk; økonomi

Technological change in the Norwegian whaling industry: A case-study in the use of patent-statistics as a technology indicator - Basberg, Bjørn L (Research Policy, 1982)
This paper presents an example of the use of patent statistics as a technology indicator in one industry. The first part deals with the problem of interpretation. Through examination of several other partial technology indicators, it is concluded that at least in this industry, patent statistics provide a reliable indicator, not only for the timing of inventions, but for the timing of innovations and diffusion as well. The reason is that the intervals between the stages in the innovation process are very short. This contradicts evidence from many other industries, and it is therefore emphasized that generalizations are unwarranted. The second part of this paper deals with the possible causes of technological change in Norwegian whaling. The methodology is inspired by J. Schmookler's work. Thus, the patents are correlated with other indicators of economic development in the industry. But while Schmookler's view is that the patent activity is determined by social demand and economic growth, the conclusions for the Norwegian whaling industry point in the opposite direction: the technological transformation that took place during the 1920s and early 1930s was forced upon the firms in their efforts to cut costs, which was achieved by rationalizing production and catching methods in line with a downward price trend for whale oil.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Moderne sydpolsproblemer - Hambro, Edvard (Samtiden, 1973)
Keywords: Antarktis; jus; politikk; økonomi

Noen problemer i den moderne hvalfangsts historie - Tønnessen, Johan Nicolay (Vestfold-minne, 1964)
Keywords: Carl Anton Larsen; Henrik Johan Bull; Svend Foyn; Sørishavet; historie; hvalfangstindustri; hvalfangstselskaper; hvalindustri; næring; pelagisk; polareksspedisjoner; økonomi

Vestfold og hvalfangsten - Bogen, Hans (Årbok for Den norske turistforening, 1947)
Keywords: Sørishavet; historie; hvalfangst; økonomi

Norges livsrom - Hoel, Adolf (Det nye Norge, 1944)
Keywords: Antarktis; hvalfangst; internasjonal politikk; polarområdene; økonomi

Japan vil overta hegemoniet i hvalfangsten! - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1939)
Keywords: Sørishavet; hvalfangst; politikk; økonomi

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Den moderne hvalfangstens kausalproblemer - Johnsen, Arne Odd (Historisk tidsskrift)
Keywords: Sørishavet; historie; hvalfangstindustri; hvalindustri; næring; pelagisk; økonomi